Positive effects of ocrelizumab in patients with familial mediterranean fever and coexistent multiple sclerosis - Caner Feyzi DEMİR,; Ferhat BALGETiR,; Özlem ETHEMOĞLU,; Dürdane AKSOY,; Filiz AKTAŞ,; Süleyman Serdar KOCA,; Mehmet Fatih YETKIN,; İrem TAŞCI, (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the effects of ocrelizumab (OCZ) on familial Mediterranean fever (FMF) attacks in multiple sclerosis (MS) patients with FMF (MS+FMF patients). Patients and methods: This retrospective observational study included 11 patients (2 males, 9 females; mean age 46.6±9.2; range, 22 to 55 years) with MS+FMF hospitalized between January 2016 and July 2019. Demographic, clinical, and laboratory parameters and patient reported outcomes were analyzed in patients treated with OCZ for 18 months. Results: Combining OCZ with colchicine in MS+FMF patients significantly reduced the frequency of FMF attacks (p=0.003) and the frequency of joint attacks (p=0.002). Consistent with the clinical improvement, the maximum serum C-reactive protein levels were significantly decreased after combination therapy compared to before combination therapy (p=0.003). MS+FMF patients reported that FMF disease activity improved after OCZ therapy (Visual Analog Scale [VAS] 74±9.6 vs. VAS 46.5±8.1 mm, p=0.003). Conclusion: Ocrelizumab therapy led to a prominent decrease in the frequency of FMF attacks, alleviated functional impairment, and improved quality of life in MS+FMF patients.